2021
DOI: 10.3390/en14040980
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Lockdown during the COVID-19 Pandemic on Electricity Use by Residential Users

Abstract: The COVID-19 pandemic and the associated lockdown can be regarded as a forced social experiment, the results of which show how to use energy under specific conditions. During this period, there was a reduction in electricity consumption at the level of the power system, but a different specificity distinguishes the group of household users. The article aims at presenting and analysing the identified issues concerning residential electricity users based on the experience from the COVID-19 pandemic lockdown. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 84 publications
(98 reference statements)
2
52
1
1
Order By: Relevance
“…As a result, an average increase of 0.3% in the hourly average energy consumption is influenced by a unit increase in the time-varying reproduction number of COVID-19. This result might seem rather low compared to the increase rate presented in previous studies [8,[14][15][16]. However, unlike other countries, Korea has responded to the spread of COVID-19 through social distancing rather than lock-down [37].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…As a result, an average increase of 0.3% in the hourly average energy consumption is influenced by a unit increase in the time-varying reproduction number of COVID-19. This result might seem rather low compared to the increase rate presented in previous studies [8,[14][15][16]. However, unlike other countries, Korea has responded to the spread of COVID-19 through social distancing rather than lock-down [37].…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, the increase in household electricity consumption would be relatively small as Koreans could move more freely during the COVID-19 pandemic than people from other countries. Furthermore, whereas previous studies showed a large percentage of change by estimated in specific industries, regions, and national sectors [8,[14][15][16][37][38][39], this study estimated the COVID-19 impact on the hourly electricity usage of each household during the social distancing period.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, Rybak and Rybak studied the impact of the COVID-19 pandemic on gaseous and solid air pollutant concentrations and emissions in Poland [47]. Bielecki et al studied the impact of the COVID-19 pandemic on electricity use by residential users [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the body of literature, there are studies of the impact of the pandemic on electricity consumption in various groups of end-consumers based on real measurements. Such research was conducted among households' inhabitants, an important group of consumers, who have changed electricity demand during the pandemic [31]. Other similar works present studies of the COVID-19 pandemic's influence on household electricity consumption in China [32], Spain [33], and Canada [34].…”
mentioning
confidence: 99%